Early lung cancer diagnosis among workers exposed to carcinogens - Consonni, Dario; Pesatori, Angela (La Medicina del Lavoro, 2018)
Following the publication of results of NLST (National Lung Screening Trial, USA) and ELCAP (Early Lung Cancer Action Project, Canada), lung cancer screening with low-dose computed tomography (LDCT) in high-risk subjects has been recommended in North-America. Conversely, the European Community has been waiting for further evidence. The recently concluded Dutch-Belgian Lung Cancer Screening trial (NELSON) confirmed the efficacy of LDCT screening in reducing lung cancer mortality. Two recent studies in the USA and Italy showed positive results in occupational settings among workers formerly exposed to asbestos. The available evidence seems to suggest the need to implement lung cancer screening programs among heavy smokers and workers substantively exposed to occupational carcinogens also in Europe, following common, standardized procedures, as indicated in a recent European position statement.